2000
DOI: 10.1128/mcb.20.15.5592-5601.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Murine Staufen Isoform Modulates the RNA Content of Staufen Complexes

Abstract: Mouse Staufen (mStau) is a double-stranded RNA-binding protein associated with polysomes and the rough endoplasmic reticulum (RER). We describe a novel endogenous isoform of mStau (termed mStau i ) which has an insertion of six amino acids within dsRBD3, the major double-stranded RNA (dsRNA)-binding domain. With a structural change of the RNA-binding domain, this conserved and widely distributed isoform showed strongly impaired dsRNA-binding ability. In transfected cells, mStau i exhibited the same tubulovesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…A 55-kDa Staufen 1 and a 53-kDa Staufen 2 isoforms are expressed in these cells, in agreement with previously reported data in other cell types (Wickham et al, 1999;Kiebler et al, 1999;Brizard et al, 2000;Duchaine et al, 2000Duchaine et al, , 2002Monshausen et al, 2001). We found that both, Staufen 1 and Staufen 2 form granules that associate with the cytoskeleton in the tubulin as well as in the actin-rich domains of the myelinating processes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A 55-kDa Staufen 1 and a 53-kDa Staufen 2 isoforms are expressed in these cells, in agreement with previously reported data in other cell types (Wickham et al, 1999;Kiebler et al, 1999;Brizard et al, 2000;Duchaine et al, 2000Duchaine et al, , 2002Monshausen et al, 2001). We found that both, Staufen 1 and Staufen 2 form granules that associate with the cytoskeleton in the tubulin as well as in the actin-rich domains of the myelinating processes.…”
Section: Discussionsupporting
confidence: 81%
“…How Staufen molecules may contribute to stress granule structure, function or dynamics is unknown. Given their ability to form granules by binding to multiple RNA targets and oligomerization via the dsRBDs (Ferrandon et al, 1994;Micklem et al, 2000;Duchaine et al, 2000), one possibility is that Staufen molecules mediate SG assembly or stability. Moreover, stress granules do not form in the absence of microtubules (Loschi and Boccaccio, unpublished results; Ivanov et al, 2003), suggesting the participation of tubulindependent motors to gather the otherwise disperse RNPs.…”
Section: Staufen As a Novel Component Of Stress Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the isolation of Staufencontaining particles by Mallardo et al (19) has confirmed the previous suggestion that there are two pools of both Staufen 1 and 2 in mammalian neurons (24,25). One pool fractionates with endoplasmic reticulum (ER) in their biochemical experiments and may represent Staufen observed in large granules that colocalize with the rough ER within the soma or at synaptic terminals (22,26,28,32,33 …”
supporting
confidence: 62%
“…All further manipulations of the brain lysates were performed at 4 o C. Cell lysates were centrifuged at 9,300 g for 10 min to remove nuclei and cell debris. After centrifugation, supernatants were incubated with rabbit polyclonal anti-Stau2 antibodies or pre-immune serum (4) for 2 hours at 4 o C, then with a 50% protein A-sepharose slurry for 2 hours at 4 o C as described before (26), except that Escherichia coli tRNA (Sigma-Aldrich) was added to a final concentration of 200 mg/ml. Immune complexes were washed five times with the lysis buffer and eluted from the resin by heating at 95 o C for 5 minutes in elution buffer (100 mM Tris-HCl pH 7.4, 200 mM DTT and 4% SDS).…”
Section: Immunoprecipitationmentioning
confidence: 99%